Cadar dan Tantangan Sosial: Studi Fenomenologi atas Kewajiban Penggunaan Cadar bagi Santriwati Ma`hadal Ulum Diniyah Islamiyah Bireuen Aceh - Muhammad Abrar Azizi; Mulyadi Mulyadi; Amiruddin Amiruddin; Putri Andriani; Athoillah Islamy (UIN Antasari Banjarmasin, 2022)
This study aims to identify the internalization process and social challenges regarding the mandatory use of the veil for the Dayah (Pesantren) Ma'hadal 'Ulum Diniyah Islamiyah (MUDI) students of the Samalanga Grand Mosque, Bireuen Regency, Aceh Province. This study uses a symbolic interactionism theory approach from George Herbert Mead. The results showed that the use of the veil for Dayah MUDI students contained the meaning of the identity symbol of Islamic teachings in totality (kāffah), preventive actions from negative actions, and at the same time Islamic da'wah bi al-ḥāl. The objectification of the meaning of the veil for the students of MUDI developed through a process of social interaction constructed by the rules in the MUDI environment. Meanwhile, female students' obstacles to using the veil outside the MUDI environment, namely the individual mental factors of students, family environmental factors, and negative social stigma factors in society. The limitations of this research can also be the object of further research. It has not yet identified the form or pattern of the environmental response of the santriwati family and the broader social community to the implementation of the mandatory use of the veil for MUDI students.